Emotional changes in people with disabilities during the COVID-19 pandemic - Šarčević Ivić-Hofman, Katarina; Veseličić, Bernarda; Smolčić Jerković, Ivana (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Given the dependence on other people and special services, and their increased susceptibility to COVID-19 infection, people with disabilities can be considered a vulnerable group in this crisis. Therefore, it was interesting to examine the differences in various emotional states in people with disabilities. Objectives. The first objective was to determine whether there was a difference between the experienced emotional states (loneliness, helplessness, insecurity, happiness, fulfillment, security) before and since the beginning of the pandemic. The second objective was to examine whether there was a difference between the experienced emotional states in relation to the number of household members. Methods. The study included a total of 230 participants, 52.2% of whom were male and 47.8% female. Data were collected through an online survey, and a small percentage of participants used the paper-pencil survey method. Data collection lasted for two months, from January to March 2021. A part of the online form contained questions about emotional states before and during the COVID-19 pandemic in relation to the number of household members. Results. The t-test for dependent samples and a series of ANOVA were conducted. The results of the conducted t-tests for each emotional state indicated a statistically significant difference in the level of experience of each observed emotional state before and since the beginning of the pandemic. The results of the ANOVA showed that those who lived with three or more household members felt less lonely, insecure and helpless, and also happier and more fulfilled compared to those who lived alone or with one or two people. Conclusion. Our role is to think, devise, advocate and implement ways to improve and encourage mental health care, especially in people with disabilities, bearing in mind possible future crisis situations.